Perception of water pollution among Malaysian university students: a case study - Austin Hew, Tze Yik; Yap, Chee Kong; Shafu Azhar, Muhammad Ezzafel; Defififaldi, Maisarah; Chew, Jia Ming; Ahmad Sapawi, Dg Khairunisa; Abdul Rahman, Mohd Nordin; Ismail, Mohamad Saupi; Wakid, Sarini Ahmad; Syazwan, Wan Mohd; Okamura, Hideo; Horie, Yoshifumi; et al. (Asia Pacific Academy of Science, 2023)
The present study aimed to understand the perception and knowledge of university students toward water pollution. In the present study, demographic profile, knowledge of water pollution, university students’ perception of water pollution and attitudes towards water pollution prevention were included in the survey questions. This survey on water pollution was conducted among a diverse group of Malaysian university students using Google Forms. The results showed that almost 50% of the respondents have basic knowledge of water pollution, and agreed that industrial activities were the main factor causing water pollution in Malaysia, followed by the accumulation of organic chemical wastes and heavy metals accumulation. It was also revealed that have shown that the water pollution campaign was a key factor to spread awareness among Malaysians and increase knowledge about water pollution problems. The results further confirmed that water pollution needs to be aware of, which showed that respondents were well aware of the water pollution issue in Malaysia and felt obligated to spread awareness and take action towards water pollution regardless of their surrounding community.